Efficacy and Safety of Ruxolitinib Cream in Atopic Dermatitis Based on Previous Medication History - Andrew Blauvelt; Howard Kallender; Daniel Sturm; Qian Li; Haobo Ren; Lawrence F. Eichenfield (Dermatology and Therapy)
Abstract Introduction For some patients with atopic dermatitis (AD), topical corticosteroids (TCS), topical calcineurin inhibitors (TCI), and systemic therapies are inadequate to control disease or are associated with adverse events (AEs). Ruxolitinib cream monotherapy demonstrated anti-inflammatory and anti-pruritic effects among patients enrolled in two pivotal phase 3 studies (TRuE-AD1/TRuE-AD2); most patients had long-term disease control with as-needed use during the 44-week long-term safety (LTS) period. This post hoc analysis explored efficacy and safety of 1.5% ruxolitinib cream by previous medication use. Methods Patients aged ≥ 12 years enrolled in TRuE-AD1/TRuE-AD2 were randomized 2:2:1 to twice-daily 0.75% or 1.5% ruxolitinib cream or vehicle cream for 8 weeks, followed by a 44-week LTS period; patients initially on vehicle were re-randomized 1:1 to either ruxolitinib cream strength. Results Within 12 months of enrollment (N = 1249), previous AD therapies were used by 89.4% of efficacy-evaluable patients applying vehicle or ruxolitinib cream (n = 725); of these, 80.4% received TCS (n = 583), 22.2% TCI (n = 161), 20.3% TCS + TCI (n = 147), and 18.9% systemic therapies (n = 137). Across previous medication subgroups, achievement of Investigator’s Global Assessment (IGA)-treatment success (IGA 0/1 with ≥ 2-grade improvement from baseline), ≥ 75% improvement in Eczema Area and Severity Index from baseline, and ≥ 4-point improvement in Itch numerical rating scale score from baseline at Week 8 did not substantially differ among patients who applied ruxolitinib cream. Outcomes were similar to those in the overall study population. At all study visits during the LTS period, > 70% of patients in each subgroup had IGA 0/1 and a low percentage (generally < 3%) of affected body surface area. Treatment-related AEs across subgroups were reported in 7.3% (n = 35/481) to 17.4% (n = 19/109) of patients. Conclusions Continuous-use ruxolitinib cream monotherapy for 8 weeks followed by as-needed use was effective and well tolerated, regardless of previous topical or systemic therapy, with outcomes similar to those achieved in the overall study population. Trial Registration ClinicalTrials.gov Identifier, NCT03745638/NCT03745651.